Relaciones tecnología y sociedad : prácticas sexuales en el mundo virtual Red Light Center (2020)
Contemporary forms of relationship with technology and digital artifacts mediate sexual encounters and practices in virtual environments. We place ourselves in the context of virtual worlds, which are 3D-looking platforms made up of computer and information technologies, where users, through their avatars, inhabit and travel through a persistent environment. Taking as a starting point Bruno Latour's definition of the social as a network whose nodes are made up of both human and non-human actors (instruments, batteries, chips or any other technological component, physical object or living being (Gonzales, 2009: 3), an autoethnography is made in the virtual world Red Light Center, which allows through experimentation not only as a researcher but also as an agent and user, to account for a determination, limitation or conduction of the users according to the conditions of the digital environment: the chat windows, gesture panels (limited repertoire of movements), action buttons and optical visualization mechanisms. At the same time, these artifacts allow socialization, visiting places within that world, talking, generating groups of similar interests and having sexual encounters, creating and recreating meanings, practices and experiments, both of sexuality and of being in the virtual.